Spatial Graduation of Fuel Taxes - Piet Rietveld; Frank Bruinsma; Daniël van Vuuren (Tinbergen Institute, 1999)
Substantial differences exist among fuel taxes in various countries. Thesedifferences represent a form of fiscal competition that has undesirable side effects because it leads to cross-borderfuelling and hence to extra kilometres driven.One possible way of solving the problem of low fuel taxes in neighbouringcountries is to introduce a spatial differentiation of taxes: low near the border and higher farther away.This paper contains an empirical analysis of the consequences of sucha spatial graduation of fuel taxes for the Netherlands.We will analyse impacts on fuelling behaviour, vehicle kilometres driven, taxreceipts, and sales by owners of gas stations. The appropriate slope of the graduation curve is also discussed. Ourconclusion is that in a small country such as theNetherlands, a spatial graduation of fuel taxes will lead to substantial changesin fuelling behaviour, even when the graduation curve is not steep. Depending on the graduation profileimplemented, the spatial differentiation of fuel tax willgive rise to substantial problems for owners of gas stations in areas withdecreasing fuel sales.
Keywords: 330; Mineralölsteuer; Räumliche Verteilung; Steuertarif; Theorie